Experimental and analytical study on uniaxial tensile property of ionomer interlayer at different temperatures and strain rates. (30th November 2020) - Chen, Suwen; Lu, Yujia; Zhang, Yang; Shao, Xiao
Highlights: Uniaxial tensile tests over wide ranges of strain rate and temperature. True stress–strain curves and characteristic mechanical parameters. Evaluation of temperature and strain rate effects. A temperature-dependent dynamic constitutive model. Abstract: The ionomer material is widely used as interlayers in the laminated glass, and its tensile property plays a decisive role in the post-fracture response of the laminated glass. Since the ionomer material is a kind of polymer, its mechanical behaviour is highly affected by strain rate and temperature. In this work, two series of uniaxial tensile tests, low strain rate series (10 −3 s −1 10 −1 s −1 ) and medium to high strain rate series (1 s −1 800 s −1 ), were conducted over a wide temperature range (−40 °C 80 °C). Details of the test setup and corresponding true stress-true strain curves are presented. Characteristic mechanical parameters are then identified to evaluate the temperature and strain rate effects. It was found that higher strain rate and lower temperature result in higher strength and stiffness but lower ductility. The material shows apparent plasticity as more than 80% deformation is unrecoverable. Based on the observations, G'Sell model is adopted to build the temperature-dependent dynamic constitutive model, which is then validated through comparison between the predicted results and the published test data.